Transitional supported housing for mental health consumers enabling personal recovery: Allowing me to be me - Dorozenko, Kate; Gillieatt, Sue; Martin, R.; Milbourn, Ben; Jennings, K. (EContent Management Pty Ltd, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. Objective: Safe, secure, affordable housing is recognised as pivotal to supporting mental health recovery. This article aims to evaluate an innovative West Australian transitional supported housing service for mental health consumers. The service offers 12-months accommodation and individually-tailored, recovery-oriented outreach support followed by six months of less intensive support. Method: Informed by the principles of personal recovery and co-production, the research team, consumers and service staff worked together to create a participatory evaluation process. Semi-structured interviews were conducted with consumers (n =8), family members (n =3), and staff (n =5) which focused on the experience and impact of the service. Data were analysed using thematic analysis. Results: Consumers and family members were satisfied with the service, particularly its person-centred and co-produced approach, and the primacy of relationships characterised by power sharing, authenticity and transparency. Having stable accommodation enabled consumers to make positive changes, including engaging in new therapies, developing independence, and pursuing study and work opportunities. When re-interviewed at least three months after leaving the accommodation, consumers reflected that the service had a significant role in facilitating their recovery and were hopeful about their future. Discussion: Housing stability alongside flexible, tailored, recovery-oriented support were central to satisfaction with the service. Challenges in securing stable, affordable housing post-service highlight the broader issue of housing affordability and supply, and highlight the need for more low cost and social housing to promote mental health recovery. As recovery is a unique, individual process, a variety of flexible supported housing options are needed.